Pengembangan E-Modul Matematika Materi Barisan dan Deret dengan Pendekatan Problem Based Learning (PBL) Kelas XI SMA - Eti Fitri Nurhandayani; Dodik Mulyono; Yufitri Yanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to produce learning media in the form of e-module in mathematics with sequence and series material with a Problem Based Learning (PBL) approach that is valid, practical, and has a potential effect on student learning outcomes. This type of research is research and development with Rowntree development model consisting of planning, development, and evaluation which has been modified by Tessmer’s evaluation (self evaluation, expert review, one-to-one, small group, and field test). The results showed that the quality of learning media in terms of the validity of language, media, and material was 0,75 (valid), 0,93 (very valid), and 0,79 (valid). From the aspect of practicality result of 71,7%. The potential effect of learning media is categorized as very good where as many as 25 students (86,21%) are included in the complete category, while as many as 4 students (13,79%) have not completed the Minimum Completeness Criteria (KKM) of 70. Keywords: E-Module development, Line and Series, PBL